Pengaruh Green Banking Disclosure (Gri Standards), Islamic Social Reporting Disclosure, dan Mekanisme Corporate Governance Terhadap Profitabilitas Bank Umum Syariah di Indonesia Periode 2020-2024 - Seftiyana Putri; Syamsul Hilal; Zathu Restie Utami (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2026)
This study examines the effect of Green Banking Disclosure (GRI Standards), Islamic Social Reporting Disclosure, and corporate governance mechanisms on the profitability of Islamic commercial banks in Indonesia for the period 2020–2024. The background of this study is based on the rapid growth of Islamic banking assets which has not been followed by evenly distributed profitability, as well as the importance of implementing sustainability practices, Islamic social reporting, and corporate governance in improving financial performance. This study aims to analyze the influence of these three variables both simultaneously and partially on the profitability of Islamic commercial banks. The research method uses a quantitative approach with a purposive sampling technique involving 8 Islamic commercial banks during the 2020–2024 period. The data used are secondary data obtained from annual reports, sustainability reports, and corporate governance reports, which are then analyzed using panel data regression with the Random Effect Model (REM). The results show that simultaneously, Green Banking Disclosure, Islamic Social Reporting Disclosure, and corporate governance mechanisms have a significant effect on profitability with an F value of 0.000068. Partially, Green Banking Disclosure (t=0.0050), Islamic Social Reporting Disclosure (t=0.0362), and corporate governance mechanisms (t=0.0016) have a positive and significant effect on profitability. The Adjusted R² value of 0.406 indicates that these three variables explain 40.6% of the variation in profitability. These findings indicate that the implementation of green banking, Islamic social reporting, and good corporate governance plays an important role in improving the profitability of Islamic commercial banks in Indonesia.